Glucose deprivation-induced disulfidptosis in human nucleus pulposus cells: a novel pathological mechanism of intervertebral disc degeneration - Shaobo Wu; Jin Wang; Minglin Wang; Kaisheng Zhou; Dageng Huang; Yilei Zhang; Haihong Zhang (Biology Direct, 2024)
Abstract Background Limited supply of certain nutrients and deregulation of nucleus pulposus (NP) plays a key role in the pathogenesis of intervertebral disc degeneration (IVDD). However, whether nutrient deprivation-induced cell death, particularly disulfidptosis, contributes to the depletion of NP cells and the development of IVDD, is unknown. Methods RNA-seq, single-cell RNA-seq, and Genome-wide DNA methylation datasets of nucleus pulposus tissue were collected for bioinformatic analysis. Predictive models of disulfidptosis related genes in IVDD were constructed by machine learning and their differential expression was analyzed. In addition, we performed cell subsets identification analysis, cell-cell communications analysis, and functional enrichment analysis of key genes in the core subset based on single-cell RNA-seq data of NP tissues isolated from one normal sample and one IVDD sample. Finally, glucose deprivation-induced disulfidptosis in human NP cells (HNPCs) was verified by various cell death inhibitors and disulfidptosis-related molecular markers. Results We found the disulfidptosis signal was significantly activated in the IVDD group. Using single-cell RNA-seq analysis, we focused on the chondrocytes and found that disulfidptosis-related genes significantly highly expressed in the IVDD C4 chondrocyte subset, which was identified as a new disulfidptosis-associated cell subset. Correlation analysis revealed the negative correlation between SLC7A11 (driving gene of disulfidptosis) and the glucose transporter GLUTs (SLC2A1-4) family genes (suppressing genes of disulfidptosis) in the IVDD group. We also found obvious cell death in HNPC upon glucose starvation, while employment of various cell death inhibitors could not inhibit glucose starvation-induced death in HNPCs. Moreover, the accumulation of disulfide bonds in cytoskeletal proteins was indicated by slowed migration in non-reducible protein blotting experiments. 2-DG, a key disulfidptosis inhibitor, significantly rescued cell death caused by glucose starvation through lowering the NADP+/NADPH ratio. Conclusions We validated the occurrence of disulfidptosis in HPNCs and identified a novel disulfidptosis-associated cell subset, followed by experimental verification of disulfidptosis in a glucose-limited context to mimic a fall in nutrient supply during the development disc degeneration. These findings provided new insights into the pathological mechanisms of IVDD and encourage us to explore potential therapeutic targets involved in the regulation of disulfidptosis for the prevention of intervertebral disc degeneration. Graphical Abstract